Treinta años desde la aplicación de las Normas Internacionales de Información Financiera en Uruguay: impacto e implicancia de su primera aplicación - Díaz Durán, Mario E. (2022)
Since the last third of the 20th century, the global accounting profession has been regulated by different organizations that have worked on the definition and elaboration of standards that facilitate the provision of high quality and comparable financial information, essentially in aspects of recognition, measurement and exposition. This process has also occurred in Uruguay, both through the issuance of professional standards issued by the Uruguayan College of Accountants, Economists and Administrators, as well as through the issuance of legal standards. Thus, various laws, decrees and pronouncements have appeared, among others, that have promoted the application of accounting standards approved by international organizations. After a description of the standards issued by the different issuing agencies, an analysis is made of the evolution of accounting standards in Uruguay with six historical periods with their own characteristics. And it concludes with two field work that covers aspects such: (i) as the impact of the application of international standards for the first time, (ii) as the level of knowledge of the standards by professionals, and (iii) the level of compliance with the university training received. The main results obtained are: that it cannot be said that there is an absence of standards, that there is a certain degree of ignorance of accounting regulations, especially International Public Sector Accounting Standards (IPSAS), that there is disagreement with the training received during the undergraduate degree, which leads to the need of updating activities and that the qual-ity of accounting information has been improved and 72% of professionals understand that the cost-benefit ratio is positive.